Intercropping Of Common Bean And Green Corn In Off-Season Crops Ii. Performance Of Maize Cultivars - dos Santos, Neli Cristina Belmiro; Arf, Orivaldo [UNESP]; Komuro, Lauro Kenji (My University, 2010)
The green corn demand, production of quality bean grain and better use of land and water resources can be used by small farmers through the intercropping of common bean and green corn in off-season crops. Field experiments were conducted in the Polo Regional Extremo Oeste- APTA, in Andradina -São Paulo State, in 2005 and 2006. The objective was to evaluate the performance of green corn cultivars grown in single crop and intercropped with common bean. The randomized blocks design with 8 treatments constituted by the combination of two corn (CATIVERDE 02 and XB 7012) and three common bean cultivars of different growth habits: IPR Colibri (I), IPR Juriti (II) and IAC Carioca (III), with four repetitions was used. The influence of the intercropping on the performance of corn was not significant. The hybrid XB 7012 was more productive in intercropping and in single crop. The hybrid production more 8000 commercials ears and lengt ears when compared with the variety. The intercropping with the IPR Juriti or IPR Colibri cultivars were the most profitable for the producer.
Consórcio de feijoeiro e milho-verde na entressafra ii. comportamento das cultivares de milho
Keywords: Intercropping; Phaseolus vulgaris l; Single crop; Zea mays l